Posted by **Anonymous** on Tuesday, December 8, 2009 at 7:33pm.

Solve the inequality.

3(h+5)<-6(h-4)

The first part, I know it 3h+15 < -6h.

- Math -
**bobpursley**, Tuesday, December 8, 2009 at 7:40pm
add 6h to both sides.

subtract 15 from both sides.

- Math -
**Anonymous**, Tuesday, December 8, 2009 at 7:43pm
The part I don't understand is if you take -6 x -4, will the thing be

3h+15 < -6h - 24 or 3h+15 < -6h + 24.

## Answer this Question

## Related Questions

- Algebra - 1. Why does the inequality sign change when both sides of the ...
- Algebra - 1. Why does the inequality sign change when both sides of the ...
- math... - A. Solve a-9=20 I did 20+9=29 29-9=20 a=29 Part b solve b-9>20 I ...
- MATH - 1~ a.) Solve a - 9 = 20 b.) Solve b - 9 > 20 c) How is solving the ...
- math - Suppose you want to cover the backyard with decorative rock and plant ...
- math 116 appendix d - b) Suppose you want to cover the backyard with decorative ...
- math prob:( - a. Solve a – 9 = 20 b. Solve b – 9 > 20 c. How is solving the ...
- Math - a.) Solve a - 9 = 20 b.) Solve b - 9 > 20 c) How is solving the ...
- MATH - a.) Solve a - 9 = 20 b.) Solve b - 9 > 20 c) How is solving the ...
- math - a. Solve a - 9 = 20 b. Solve b - 9 > 20 c. How is solving the ...